ASSESSMENT OF ANTIOXIDANT STATUS OF RATS AT THE BACKGROUND OF CONSUMPTION OF SPECIALIZED CHOCOLATE WITH LEAD ACETATE EXPOSURE (Experimental biology, 2025)
This article presents the results of experimental research on the assessment of the antioxidant status of animals consuming specialized chocolate developed from mare’s milk, enriched with resveratrol and vitamin E. The study demonstrated that after 30 days of intragastric lead acetate administration, rats showed an activation of lipid peroxidation processes in their blood serum. This was accompanied by the accumulation of both primary and secondary products—malondialdehyde and diene conjugates—as well as a decrease in vitamin E content and total antioxidant activity in the blood.Excessive accumulation of peroxidation products was accompanied by increased catalase activity and decreased superoxide dismutase activity. It is noteworthy that all observed changes in the mentioned indicators were statistically significant. The reduction in antioxidant status highlighted the need to enrich the diet of animals under lead intoxication conditions with products containing high levels of antioxidants and antioxidant substances.In this study, the effect of specialized chocolate enriched with mare’s milk, resveratrol, and vitamin E on the antioxidant status of animals exposed to toxic lead acetate administration was evaluated. After 30 days of the experimental period, the consumption of 5 grams of specialized chocolate per day by the rats was found to improve their antioxidant status. This improvement was reflected by a reduction in lipid peroxidation products in the blood serum, increased superoxide dismutase activity, decreased catalase activity, and higher levels of vitamin E and total antioxidant activity in the serum.The obtained results indicate the beneficial effect of the chocolate on the processes of lipid peroxidation and antioxidant defense, supporting its potential use for preventive purposes in cases of lead salt poisoning.
Keywords: antioxidant status; chocolate; mare’s milk; resveratrol; vitamin E; toxic intoxication